2016
DOI: 10.1021/acs.jpcb.6b02839
|View full text |Cite
|
Sign up to set email alerts
|

Homolytic Cleavage of Both Heme-Bound Hydrogen Peroxide and Hydrogen Sulfide Leads to the Formation of Sulfheme

Abstract: Many heme-containing proteins with a histidine in the distal E7 (HisE7) position can form sulfheme in the presence of hydrogen sulfide (H2S) and a reactive oxygen species such as hydrogen peroxide. For reasons unknown, sulfheme derivatives are formed specifically on solvent-excluded heme pyrrole B. Sulfhemes severely decrease the oxygen-binding affinity in hemoglobin (Hb) and myoglobin (Mb). Here, use of hybrid quantum mechanical/molecular mechanical methods has permitted characterization of the entire process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 90 publications
1
24
0
Order By: Relevance
“…It has also been proposed that, in the case of myeloperoxidase, the presence of a sulfonium ion linkage between a methionine and the heme ring determines that, in contrast to lactoperoxidase, the sulfheme cannot be formed [106]. Computational simulations suggest that sulfheme formation occurs through a concerted interaction between the distal histidine, H 2 S, and a ferric-bound hydroperoxide to form oxoferryl compound II, H 2 O and HS•; the latter subsequently adds to a specific pyrrole site [113].…”
Section: Oxidizing Species In Biology and Their Reactions With H2smentioning
confidence: 99%
“…It has also been proposed that, in the case of myeloperoxidase, the presence of a sulfonium ion linkage between a methionine and the heme ring determines that, in contrast to lactoperoxidase, the sulfheme cannot be formed [106]. Computational simulations suggest that sulfheme formation occurs through a concerted interaction between the distal histidine, H 2 S, and a ferric-bound hydroperoxide to form oxoferryl compound II, H 2 O and HS•; the latter subsequently adds to a specific pyrrole site [113].…”
Section: Oxidizing Species In Biology and Their Reactions With H2smentioning
confidence: 99%
“…The results supported the unique function of E7 histidine in sulfheme formation. 25,28 The NMR of several sulfMbCN complexes revealed that there are three isomeric forms of the chlorin structure in sulfMb derivatives named S A Mb, S B Mb, and S C Mb (Figure 1, inset). 20−24 The S A structure is an episulfide formed across the C3−C4 double bond, S B is characterized as a "ring opened episulfide", and S C is a thiochlorin structure.…”
Section: ■ Introductionmentioning
confidence: 98%
“…As previously reported, we performed a PM6/CHARMM molecular dynamics (MD) simulation for a model of the HbI GlnE7His mutant. 28 This HbI mutant has an active site and experimentally determined properties very similar to myoglobin (Mb). A snapshot from the 1.4 ns (ns) PM6/MM MD simulation was used as a starting model for investigation into the mechanism of sulfheme formation using a hybrid B3PW91/MM potential energy function.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such environments are known 12 to initiate sulfheme formation reaction in myoglobin and hemoglobin in the presence of H2S. Furthermore, heme radical states are invoked 13 in the sulfheme formation mechanism. In a different mechanism, 14 H2S was shown to react with heme via HS -, i.e.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%